Enhanced and sustained pesticidal activity of a graphene‐based pesticide delivery system against the diamondback moth Plutella xylostella. Issue 12 (15th September 2022) - Liu, Jianfeng; Luo, Yi; Jiang, Xuefeng; Sun, Guangjun; Song, Saijie; Yang, Maofa; Shen, Jian
Abstract: Background: Traditional abamectin (Abm) formulations have several shortcomings, such as low water solubility, burst release behavior, poor photostability, and short persistence periods, which decrease their pesticidal activity and the risks they pose to the environment. Nanomaterial‐based pesticide delivery systems (PDSs) provide new strategies for the efficient and safe application of pesticides. Here, we developed Abm‐loaded graphene oxide (Abm/GO) as a PDS for the sustained release of Abm, which shows enhanced control efficacy against Plutella xylostella . Results: The hydrophobic Abm molecule was effectively loaded on GO nanocarrier by a physisorption method, which formed a uniform and stable Abm/GO nanoformulation. GO possesses high adsorption capacity and can effectively load Abm. The Abm/GO nanoformulation shows enhanced water dispersion stability and can remain stable during a 2‐year storage period in contrast to the water‐insoluble Abm. In addition, the Abm/GO nanoformulation exhibits sustained pesticide release behavior and possesses significantly improved anti‐ultraviolet properties. Thus, the Abm/GO nanoformulation shows superior pesticidal activity compared with Abm. Abm/GO showed negligible toxicity to maize seedlings, and its GO nanocarrier can reduce the cytotoxicity of Abm to A549 cells. Conclusion: GO‐based PDSs can effectively overcome the disadvantages of traditional pesticides, such as their insolubility, burst release behavior, instability, and short persistence period. GO shows much future promise in agriculture in light of its industrialization potential. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Abamectin (Abm) is a broad‐spectrum and highly efficient biological pesticide. Graphene oxide (GO) has high biosafety, aqueous solubility, and drug loading capacity. The hydrophobic pesticide Abm can be effectively loaded on GO and form nanoformulations with stable water dispersion, slow‐release, and anti‐ultraviolet properties. The high toxicity of Abm to Plutella xylostella is sustained in the Abm/GO nanoformulation. Abm/GO showed negligible toxicity to maize seedlings, and its GO nanocarrier can reduce the cytotoxicity of Abm to A549 cells.